Students’ Perceptions of The Implementation of Communicative Language Teaching (CLT) in Enhancing Writing Argumentative Competence in Twelfth-Grade Students of MAN 2 Bengkulu - Putri, Nabila Fasyiha; Zasrianita, Fera; Serasi, Reko (The Future of Education Journal, 2025)
This study examines twelfth-grade students’ perceptions of Communicative Language Teaching (CLT) in improving their argumentative writing skills at MAN 2 Bengkulu. The research aims to explore students’ views on how CLT enhances their engagement, motivation, and writing ability, as well as the challenges and benefits they experience. Using a mixed-methods design, data were collected through questionnaires, interviews, and documentation from five classes. The findings revealed that students showed highly positive perceptions of CLT, with average scores ranging from 79.4% to 86.9%. They felt that CLT made learning more interactive, enjoyable, and student-centered, helping them express ideas and construct arguments more logically. Despite difficulties such as limited vocabulary and grammar mastery, students believed CLT improved their confidence, participation, and writing skills. Overall, CLT proved effective in enhancing students’ communicative competence and argumentative writing in English learning.